Краєзнавчі дослідження професора Г.Д. Казьмирчука (до 75-річчя від дня народження) - Гончаров, О.; Казьмирчук, М. (Краєзнавство, 2019)
У статті аналізується життєвий та творчий шлях відомого українського історика, професора
Григорія Дмитровича Казьмирчука, якому виповнилося 75 років. Він присвятив понад 40 років викладанню у Київському національному університеті імені Тараса Шевченка. Г.Д. Казьмирчук – знаний декабристознавець, історіограф, бібліограф та краєзнавець, активний учасник Національної спілки краєзнавців України. Він автор понад 560 наукових праць, половина з яких присвячена краєзнавчій
тематиці. Його краєзнавчі роботи спрямовані на висвітлення проблем, пов'язаних з пам'ятниками і
пам'ятними місцями декабристів в Україні, історією рідного села Кальника, зокрема його славетною
козацькою минувшиною та вічною пам'яттю легендарного Кальницького козацького полку, генеалогією
власного роду, а також біографіями видатних декабристознавців та кальничан. The article analyzes the life and creative path of the outstanding Ukrainian historian, Professor Grygorii D.
Kazmyrchuk, who turns 75 years old. He has devoted more than 40 years of teaching to Taras Shevchenko Kyiv National
University, a well-known Decembrists-scholar, historiographer and local historian. Grygorii D. Kazmyrchuk
is an active member of the Union of Local History of Ukraine. He has more than 560 scientific works, half of which
devoted to local lore problems. His local lore work is aimed at highlighting problems of the monuments and memorable
places of the Decembrists in Ukraine, the history of the native Kalnik village. His work is aimed at studying
its glorious Cossack past and the eternal memory of the legendary Kalnitsky Cossack Regiment, the geneology of
his own family, as well as biographies of prominent researchers of the Decembrists and Kalnik villagers. Grygorii
D. Kazmyrchuk is the founder of the School of Decembrists Studies at the Taras Shevchenko National University of
Kyiv. He is an elder of the Kalynitsky Cossack Regiment and an honored researcher of local lore of Ukraine. He is
the author of regional studies on the history of the Kalnyk village and the Kalnitsky Cossack Regiment.